The Effects of Financial Development on Foreign Direct Investment - Desbordes, Rodolphe; Wei, Shang-Jin (World Bank Group, Washington, DC, 2014)
This paper examines how financial development influences foreign direct investment. The direct and indirect sector-specific effects that source countries' financial development and destination countries' financial development can have on foreign direct investment are first identified in a conceptual framework. The presence and relative strength of these various channels of influence at the different margins of foreign direct investment are then empirically investigated using unique and underexploited sector-specific bilateral panel data on greenfield foreign direct investment over the period 2003-2006. Causality is established by applying a difference-in-differences approach that exploits the variation in financial vulnerability across manufacturing sectors. The overall effects of higher source countries' financial development and destination countries' financial development on the relative volume of bilateral foreign direct investment in financially vulnerable sectors are large, positive, and complementary. These effects appear to operate mainly at the intensive margin rather than at the extensive margin of foreign direct investment. There is also evidence of direct and indirect effects of financial development. The key findings are robust to the use of data on the number of bilateral Mergers&Acquisitions transactions. Overall, the empirical results unambiguously indicate that a sophisticated and well-functioning financial system in source and destination countries greatly facilitates the international expansion of firms through foreign direct investment, especially in financially vulnerable sectors.